LEGAL ANALYSIS OF COPYRIGHT INFRINGEMENT IN COMMERCIAL USE OF SONGS AND/OR MUSIC (CASE STUDY OF MIE GACOAN FRANCHISE ROYALTIES) - Daniel Vinato; Ismail Koto (Inspiring Law Journal, 2026)
This study analyzes copyright infringement in the commercial use of songs and/or music and its legal liability implications, using a case study of royalties in the Mie Gacoan franchise. Playing songs in commercial business spaces constitutes a form of exploitation of the creator's economic rights, requiring a license and royalty payments. However, in practice, some businesses still use musical works without permission or without fulfilling their royalty payment obligations, resulting in legal issues and economic losses for the creator. Normatively, the obligation to pay royalties is regulated by Law Number 28 of 2014 concerning Copyright and Government Regulation Number 56 of 2021 concerning Management of Song and/or Music Royalties. These provisions emphasize that any use of songs and/or music for commercial purposes must go through a licensing mechanism and royalty payments to the creator or through a Collective Management Institution. Violations of these provisions have the potential to result in legal consequences, both in the civil and administrative realms. This study uses a normative juridical method with a statutory and conceptual approach. Primary, secondary, and tertiary legal materials were collected through literature studies and analyzed qualitatively to examine the forms of violations and legal accountability mechanisms that can be applied to business actors who do not fulfill royalty obligations. The results of the study indicate that the commercial use of songs without a license constitutes a violation of the creator's economic rights and fulfills the elements of an unlawful act as regulated in Article 1365 of the Civil Code. Legal protection for creators can be achieved through lawsuits for damages, termination of use of the work, and the obligation to pay royalties through a Collective Management Institution. This study confirms that compliance with royalty obligations is part of the legal responsibility of business actors in ensuring legal certainty and justice for creators in the copyright protection regime.